Social Norms, Perceptions, Taxpayer Behavior, Tax Digitalization and Taxpayer Compliance - Ni Putu Desriana Dewi; Gede sri darma (Jurnal Indonesia Sosial Teknologi, 2024)
Considering that the level of tax compliance is important for the country as outlined above, research is needed that can provide solutions to reducing and even eliminating the gap between the ideal conditions of taxpayer compliance and the reality on the ground. This study uses a quantitative research design. The quantitative instrument used was in the form of a questionnaire distributed to prospective respondents. The data was analyzed using SmartPLS software with SEM (Structural Equation Modelling) analysis techniques. This study uses purposive sampling in the determination of samples. Typical case sampling is used in this study, namely, prospective respondents are taxpayers who come directly to the tax office to report their tax returns even though at the time of reporting their tax returns at the tax office, they still use digital tax services such as e-filling or e-form. The results of this study show that three of the four research variables used have a significant effect on taxpayer compliance. For future researchers, there is still a lot of room to continue research that explores other factors that affect the relationship between attitudes to behaviour, social norms and perception of behavioural control towards taxpayer compliance in the hope that the results can be used in efforts to improve tax compliance.